The Collapse of a Collective Society: Teuchitlán in the Tequila Region of Jalisco, Mexico - Heredia Espinoza, Verenice Y. (Frontiers in Political Science, 2022)
Cross-cultural research on ancient societies demonstrates that collective social formations tend to experience a more sudden collapse with relatively catastrophic effects compared to formations low in collectivity. The demise of collective formations often involves more pronounced social unrest and a more complete disintegration of the agrarian and sociopolitical systems. This article further probes this general finding using the case of Teuchitlán, in the Tequila region of Jalisco, Mexico, which lasted for 700 years, from 350 B.C.E. to about 450/500 C.E., when it suddenly disappeared. It was characterized by power-sharing among multiple groups whose leaders employed varied political strategies. Structurally, Teuchitlán aligns with some of the precepts of collective action and good government, as it was inwardly focused and placed great emphasis on the joint production of the polity's resources, especially agriculture, as well as the equitable distribution of benefits, such as community feasting and ritual, and some form of political participation or voice (e.g., power-sharing). Scholars working in the area have invoked various environmental factors, demographic movements, natural disasters, the collapse of central places, and a breakdown in trade connections, among others, as causes of Teuchitlán's disintegration—and the answer may indeed lie in a combination of these phenomena. This article explores the major shifts in the institutions that comprised Teuchitlán, thereby presenting an alternative view of its nature and disappearance. Settlement patterns, architectural differences, ceramic decoration and vessel forms, and lithic technology from the period following Teuchitlán's collapse suggest major changes in ideology, economy, and politics. The placement of large centers along trade routes, coupled with increased control of interregional exchange, indicates a shift toward direct, discretionary control of polity revenues by political leaders with little benefit for the populace. As part of these changes, the human landscape became more ruralized. Teuchitlán is comparable to other well-known cases in the world where more collective forms of political organization met a similar fate, such as Chaco Canyon (Southwest USA), Jenne-jeno (Mali), and the Indus Civilization.